Comparing Flexible Ureteroscopy and Percutaneous Nephrolithotomy for Lower Pole Stone - Pandu Ishaq Nandana; M. Hairul Umam (Faculty of Medicine Universitas Mataram, 2022)
A total of 10 comparative studies involving 1241 participants with lower pole calyx stone size 1.0 – 3.0 cm were included for this systematic review. Our review found out that stone free rate PCNL procedure range around 83.3% - 98.3% and FURS procedure range around 78.6% - 93.2%; operative time of PCNL procedure range around 46.2 + 24.3 to 85.5 + 41.1 minutes meanwhile FURS procedure range around 55.8 + 11.4 to 123.0 + 57.4 minutes; hospital stay of PCNL procedure range around 0.3 + 0.04 to 5.3 + 1.20 days and hospital stay of FURS procedure range around 0.16 + 0.04 to 3.2 + 0.52 days; and complications rate after PCNL procedure range around 4.4% - 25% and after FURS procedure range around 4.6% - 21.6%. Most of studies shown that PCNL procedure have higher stone free rate, shorter operative time, longer hospital stays and higher complications rate compared against FURS procedure.